Práticas pedagógicas no Centro Socioeducativo Tamoios: avanços, retrocessos e desafios para uma pedagogia humanizadora - Nogueira, Rivanil Rubens (2022)
This paper aims to describe and analyze the pedagogical practices promoted byFundaçãoCasa in 2019, having as research locus the Tamoios socio-educational center of themunicipality of São José dos Campos (S.P). It seeks to highlight against the paths carriedoutby educators who seek to develop socio-educational actions based on humanizing pedagogicalpractices. For this, the research trajectory conducted in the quantitative and qualitativescope,covered bibliographic and documentary research, as well as the field research work, wherethetechniques of participant observation, interviews and action research were used. Thethemeaddresses the multiple faces of the experience of institutional daily life. The researchrevealedthat pedagogical practices are the essence and meaning of existence of a socio-educationalinstitution. This can be found in the official discourse through the legal andguidingdocuments of the Fundação Casa that is based on the Doctrine of Integral Protection.However, the field research showed contradictions and gaps that permeate the dailylivesofadolescents and educators who experience a context still with repressive and violent actionsbased on the Doctrine of National Security of control and discipline and that has newformsofdomination such as the conformation of adolescents the citizen rules for individual success.However, in this scenario, the research revealed forms of resistance of educatorsandadolescents through the exercise of humanizing pedagogical practices capable of promotingcircumstances of critical reflections and transformative actions for the birth of the newmanbased on the assimilation of new values that favor the human and the collective